Efeito de um complexo multienzimático sobre desempenho zootécnico e parâmetros sanguíneos de leitões na fase inicial - Pereira, Lilian Kelly (2017)
The high costs of pig breeding are one of the factors that most affect the activity, and the nursery phase is one of the most critical stages of production. Faced with this, producers seek food that ensures the efficiency of production and reduce the risks of this phase. The use of additives such as enzymes can make feed nutrients more digestible and improve animal performance. The objective of the present study was to evaluate a multienzymatic complex in the diet of piglets in the initial phase (15 to 30 kg). The experiment was conducted at the Universidade Tecnológica Federal do Paraná, Campus Dois Vizinhos, at the Swine research and Training Unit (UNEP). There were four treatments, T1: Negative Control + Complex Multiezimatic (CME); T2: Negative Control; T3: Positive Control + CME e; T4: Positive Control. A total of 80 piglets were used, 40 castrated males and 40 females from a commercial line, with a mean initial weight of 16.88 kg + 2.69 kg, housed in masonry bays. The animals were weighed individually each week to measure the weight gain, the rations provided and the leftovers were weighed for determination of feed intake and feed conversion. The experimental design was randomized blocks, in a 2x2 factorial scheme, two control diets (positive and negative) and two levels of enzymes added to the diet (0 and 50 g / t). Performance data and blood parameters were subjected to analysis of variance and treatment effects were compared through factorial analysis to evaluate the effects of CME. By means of the mean weight obtained at the end of the experiment, 40 animals were selected, of which 10 were used to collect 10 mL of blood for analysis of blood parameters. In order to evaluate the economic viability, the raw material used to obtain the experimental feed costs was calculated. The cost of the ration per kilogram of live weight gained, the Economic Efficiency Index (IEE) and the Index Of Cost (CI). The results showed that there was no significant difference of the treatments (P <0.05) on the variables of growth performance and the blood parameters of piglets in the initial phase. The economic viability was better in negative control diets supplemented with CME when compared to the other experimental diets. Therefore, we can conclude that supplementation of CME in negative control diets do not has negative effect on growth performance and health of animals and reduces the cost of production.